Advancing Novel Strategies against Post-surgical Tendon Adhesion Bands, Exploring New Frontiers - Alaei, Maryam; Abdulhasan, Doaa Jawad-Kadhim; Barjasteh, Amirhossein; Al-Asady, Abdulridha M.; Latifi, Hanieh; Vahedi, Ehsan; Avan, Amir; Khazaei, Majid; Ryzhikov, Mikhail; Hassanian, Seyed Mahdi (Current Pharmaceutical Design, 2024)
Current interest in adhesion formation stems from its global impact on the function and quality of life, spanning a spectrum of subtle impairments to significant disabilities, based on the affected area and the extent of adhesion. Yet therapeutic agents are restricted to prophylactic anti-inflammatories, revision surgeries, and biological and physical techniques, none of which grant a decent outcome. Recent advancements in tissue- engineered biomaterials, drug delivery systems, and fabricating technologies such as nanoparticles, hydrogels, and weaving or braiding demonstrate potential for improved outcomes. However, none of the mentioned methods have reliable outcomes, thus this study aims to elucidate the mechanisms involved in the pathophysiology of tendon adhesion and post-surgical adhesion band formation (PSAB), with a closer look at inflammatory pathways stimulating the process. This article consolidates information on diverse therapeutic and prophylactic methods and cutting-edge technologies, aiming to provide a comprehensive update on this topic, and providing researchers an avenue for new and innovative ideas for further investigations.
Keywords: quality of life